Leadership in the creation of excellent work culture. - Hamzah, Mohd Sahandri Gani; Sin, Ishak; Abdullah, Saifuddin Kumar (EuroJournals, Inc., 2009)
Malaysia has set 2020 as the target year to become a developed nation. There are only twelve years left for this to be achieved. Since the launching of the objective, much action has been taken to achieve this status. These actions are in the area of economy, social justice, spiritual strength, morality and ethics (Malaysia 1996). In order to become developed in this globalized era, Malaysia must become the chief player in producing products that are of world class standard. These kinds of products can only be produced if diligence and seriousness, along with efforts of creativity and innovation, exist in members of organizations. According to theory, diligence and seriousness will only come about when an excellent work culture has become the core of the organizational culture in any given organization (Md Zabid, Sambasivam, Azmawani (2004). To achieve this objective is not easy. Problems in delivery in Malaysia today has become an increasing concern, to the extent that the government is obliged to build a group of workers to ensure the implementation of work is more efficient and productive (New Straits Times, 8 February 2007:1). Even though the government of Malaysia has given instructions through Pekeliling Kemajuan Perkhidmatan Awam (PKPA) that every government agency is to regulate the quality of work culture on a daily basis since 1991, these instructions seems ineffective. Now questions have been raised on how many agencies are really putting into practice the PKPA instructions. How many government agencies are able to be accredited by ISO9000? What about Kumpulan Meningkat Mutu Kerja (KMK) and TQM? Through the author's experience, the implementation of PKPA is not encouraging. This question is if the existence of this problem is caused by organizational culture or work culture.